Prostate-specific kallikrein-related peptidases and their relation to prostate cancer biology and detection - Thorek, Daniel L. J.; Evans, Michael J.; Carlsson, Sigrid V.; Ulmert, David; Lilja, Hans (Thrombosis and Haemostasis, 2013)
Kallikreins are a family of serine proteases with a range of tissue-specific and essential proteolytic functions. Among the best studied are the prostate tissue-specific KLK2 and KLK3 genes and their secreted protease products, human kallikrein 2, hk2, and prostate-specific antigen (PSA). Members of the so-called classic kallikreins, these highly active trypsin-like serine proteases play established roles in human reproduction. Both hK2 and PSA expression is regulated by the androgen receptor which has a fundamental role in prostate tissue development and progression of disease. This feature, combined with the ability to sensitively detect different forms of these proteins in blood and biopsies, result in a crucially important biomarker for the presence and recurrence of cancer. Emerging evidence has begun to suggest a role for these kallikreins in critical vascular events. This review discusses the established and developing biological roles of hK2 and PSA, as well as the historical and advanced use of their detection to accurately and non-invasively detect and guide treatment of prostatic disease.